Stereovision in children with congenital myopia and in those with myopic amblyopia (Ukrainian Journal of Ophthalmology, 2026)
Background: Stereovision is a reliable and sensitive indicator of the ability to analyze spatial relationships. The ability to fuse images that fall on either corresponding or slightly disparate retinal elements within Panum’s fusional area results in binocular appreciation of visual object in depth (i.e. in the third dimension) and in the ability to orientate oneself in space. While studying the pathophysiological mechanisms of abnormal visual function, scientists analyze the system at the level of an individual channel, and investigate the interaction between channels. Despite the progress made so far in studying stereovision, it is not known whether the stereoacuity test scores for children with congenital myopia differ from those for children with myopic amblyopia in the absence of fundus changes.Purpose: To investigate stereovision in children with congenital myopia and in those with myopic amblyopia with the use of various stereoacuity tests.Materials and Methods: We studied 52 children (104 eyes; age, 5 to 18 years) who were under observation. These included children with amblyopia (54 eyes) and myopes without amblyopia (50 eyes).  Mean myopia in children with amblyopia was somewhat higher than in those with congenital myopia (7.01 ± 4.2 D vs 6.5 ± 4.0 D). In total, 22 eyes had astigmatism greater than 4.0 D, and 7 eyes had anisometropia greater than 2.0 D. Mild amblyopia (with BCVA greater than 0.4), moderate amblyopia (with BCVA of 0.2 to 0.4) and severe amblyopia (with BCVA of 0.05 to 0.15) was found in 32 eyes, 9 eyes, and 9 eyes, respectively.Results: In 68.9% of children with congenital myopia, the stereo threshold measured with Titmus contour tests was ? 100 arcsec. In addition, in 85.4% of children with congenital myopia, the stereo threshold measured with Lang II random-dot test was 400 to 600 arcsec. The length of time till the occurrence of a stereo effect in 84.2% of children was less than 20 s.Conclusions: Stereovision was better in children with congenital myopia than in those with myopic amblyopia. Contour and random-dot stereotests found that the former children had better stereovision than the latter. A length of time (from presentation of a test object to the occurrence of a stereo effect) of less than 20 s was found in 88.46% of children with congenital myopia, and in 16.6% of those with myopic amblyopia.
Keywords: congenital myopia; myopic amblyopia; stereo vision; Lang II random-dot test; Titmus stereo fly test; binocular functions